Circulação de ar na península de Tróia e costa da Galé - Neto, Carlos Silva (2000)
AIR FLOW OVER THE TRÓIA PENINSULA AND THE COSTA DA GALÉ – In the summer, the Portuguese western coast is characterised by an evident dominance of north and northwest wind directions. Due the influence of the Arrábida mountain, the north wind suffers a deflection and blows from the west, southwest or even south over the Tróia Peninsula, where in the summer months there is a high frequency of wind directions between west and south. This deflection is much more frequent and better marked at night than at daylight. At daylight the strong north wind is channelled through a valley between Palmela hill and the Louro mountain and frequently blows over the Tróia Peninsula, in directions between north-northeast and north-northwest. At night, north and northwest wind speeds are generally lower and west and south winds blow all over the Tróia Peninsula towards Carvalhal, as result of the deflection caused by the Arrábida and Cabo Espichel. The wind directions between west and south, frequent at night on the Tróia Peninsula, are also intensified by the difference of temperature between the cool ocean and the warm water of the estuary.